الأفعال الكلامية الإنجازية في حوار فيلم "قيامة أرطغرل" الحلقة الأولى - Syamsi Setiadi; Muhammad Kamal; Annisa Ayu Rahmah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
This study aims to obtain a clear description of the form and function of illocutionary speech acts in the dialogue of the film "Qiyamatu Ertugrul" episode 1. The method used in this research is descriptive qualitative method. The research instrument is the researcher herself is assisted by a classification table which contains the types of illocutionary speech acts and their fusions. Thus the researcher got the results that illocutionary speech acts in the dialogue of the film "Qiyamatu Ertugrul" episode 1, are as follows: 19 assertive speech acts with a percentage of 21% consisting of a statement function of 16 utterances and 3 explanations of 3 speeches. Commissive speech acts were 8 utterances with a percentage of 8% consisting of the promise function of 6 utterances and threats of 2 utterances. The directive speech acts were 47 speeches with a percentage of 53% consisting of the function of forcing 1 speech, giving advice as much as 1 speech, forcing 2 speeches, praying for 2 speeches, asking for 3 speeches, offering as many as 3 speeches, begging as much as 5 utterances, and ordered as many as 30 speeches. Expressive speech acts were 15 utterances with a percentage of 17% consisting of praising 6 utterances, thanking 5 utterances and congratulating 4 utterances. There are also declarative speech acts that are not found in the dialogue of this film.